Urine Angiotensinogen and Salt- and Potassium-Sensitivity of Blood Pressure. (June 2015) - Chen, Jing; Rebholz, Casey M.; Zhao, Qi; Chen, Ji-Chun; Li, Jianxin; Cao, Jie; Navar, L. Gabriel; Hamm, L. Lee; Gu, Dongfeng; He, Jiang
Abstract : Background: Urinary excretion of angiotensinogen (UAGT) has been proposed as a biomarker of intrarenal renin-angiotensin system activity. Objective: We investigated the association between UAGT and salt- and potassium-sensitivity of blood pressure (BP) among Genetic Epidemiology Network of Salt Sensitivity (GenSalt) study participants. Method: The intervention consisted of a 7-day low-sodium diet (51.3 mmol sodium/day), 7-day high-sodium diet (307.8 mmol sodium/day), and 7-day high sodium diet with potassium supplementation (307.8 mmol sodium and 60 mmol potassium/day). 24-hour UAGT was estimated at baseline and at the end of each intervention for 100 randomly selected participants. Result: Median UAGT (μg/24 hours) and UAGT-to-creatinine ratio (UAGT/Cr, μg/g) were significantly reduced during low-sodium and potassium supplementation interventions and increased during high-sodium intervention (both p  = 0.01). Baseline log-transformed UAGT and UAGT/Cr ratio were significantly positively associated with BP at baseline and at the end of each intervention. For example, one standard deviation higher log-UAGT/Cr ratio (1.2 μg/g) was associated with a 5.0 mmHg (95% confidence interval: 2.3, 7.8) higher systolic BP at the end of the high-sodium intervention, after adjusting for multiple covariates ( p  = 0.003). In addition, one standard deviation higher log-UAGT/Cr ratio was associated with a 1.6 mmHg increase in age- and sex-adjusted systolic BP from the low-sodium intervention to the high-sodium intervention (95% confidence interval: 0.1, 3.1; p  = 0.04). This association was no longer statistically significant after multivariable adjustment. Conclusion: These data indicate that elevated UAGT are associated with BP sodium-sensitivity. Augmentation of intrarenal renin-angiotensin system activity may play an important role in developing salt-sensitive hypertension.